Problem Loans in Banks and Implementation of Good Corporate Governance (GCG) - Deisy Kalangi; Denny Tewu (Budapest International Research and Critics University, 2022)
Bank Maybank Indonesia is an Indonesia-based company primarily engaged in the banking sector. The Company's business activities are divided into three business segments: Global Banking which includes corporate banking, transaction services and global markets; Community Financial Services (CFS) which is an integration of retail and business banking functions that include third party funds, business loans, micro small and medium business loans, home ownership loans and others, as well as Islamic Banking services. In the Banking Industry, Good Corporate Governance is an important factor in maintaining the trust and confidence of shareholders and customers. The application of the principles of good corporate governance in the bank management system is very important in increasing the success of a company engaged in banking. This study aims to identify and analyze non-performing loans in Micro, Small and Medium Enterprises at banks and to determine the efforts made in dealing with the occurrence of Non-performing Loans in Micro, Small and Medium Enterprises at banks. This type of research will be carried out using descriptive research methods with a quantitative approach. The results of this study will show that the application of credit risk management which includes active supervision of the board of commissioners and directors, policies, procedures and limit setting, identification, measurement, monitoring, and credit risk management information systems, as well as an internal control system for non-performing loans at PT. Maybank Indonesia. Based on this research, banks can maintain the independence of credit staff and improve the credit monitoring process.